2008
DOI: 10.1007/s11524-008-9306-7
|View full text |Cite|
|
Sign up to set email alerts
|

Neighborhood Effects on an Individual’s Health Using Neighborhood Measurements Developed by Factor Analysis and Cluster Analysis

Abstract: This study suggests a multivariate-structural approach combining factor analysis and cluster analysis that could be used to examine neighborhood effects on an individual's health. Data were from the Taiwan Social Change Survey conducted in 1990, 1995, and 2000. In total, 5,784 women and men aged over 20 years living in 428 neighborhoods were interviewed. Participants' addresses were geocoded with census data for measuring neighborhood-level characteristics. The factor analysis was applied to identify neighborh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 29 publications
0
23
0
1
Order By: Relevance
“…Integrating these two methods may better explain the diversity and natural grouping of behaviors and may help overcome limitations of only using either factor or cluster analysis. 45 This same approach has been used to define primary health-care patterns in children, 46 to propose a neighborhood socioeconomic typology based on the social characteristics of the population, 45 and to identify accident patterns at work 47 or on the road. 48 One of the strengths of this study is that we used a detailed physical activity questionnaire specifying the types of LTPAs performed during the preceding year and the duration of each reported activity.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating these two methods may better explain the diversity and natural grouping of behaviors and may help overcome limitations of only using either factor or cluster analysis. 45 This same approach has been used to define primary health-care patterns in children, 46 to propose a neighborhood socioeconomic typology based on the social characteristics of the population, 45 and to identify accident patterns at work 47 or on the road. 48 One of the strengths of this study is that we used a detailed physical activity questionnaire specifying the types of LTPAs performed during the preceding year and the duration of each reported activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous empirical studies [30,51] have suggested that the K-means is best for recovering the true groupings of data if a non-randomized starting point is assigned. A K-means clustering method does not require the computation of all possible distances of analyst neighborhoods.…”
Section: Cluster Analysis Of Spatial Patterns Of Overall Natural Envimentioning
confidence: 99%
“…Particular neighborhood type(s) are responsible for causing a variety of social problems, including crimes [39]. The same can be true for the inhabitants' propensity to catch different types of mental or physical diseases [40]. Moreover, the emotional trauma of living in a high crime neighborhood changes children's outlook and influences their behavior towards violence, danger, and unjust acts [41].…”
Section: Neighborhood Effectsmentioning
confidence: 99%
“…and physical condition, and behavioral and psychological characteristics), and their vulnerability towards chronic diseases could be investigated by exploring neighborhood effects [40]. While developing a mode choice model, this study tends to reflect the interrelationships between people's characteristics, social ties, and family bonding that may fluctuate on their spatial distribution.…”
Section: Neighborhood Effectsmentioning
confidence: 99%
See 1 more Smart Citation